VERBA FRASAL DALAM NOVEL THE STARS SHINE DOWN KARYA SHIDNEY SHELDON - Mawikere, Michael Frisky (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI)
ABSTRACT Â ThisÂ researchÂ entitled â€œPhrasalÂ VerbsÂ inÂ theÂ novelÂ â€œTheÂ StarsÂ ShineÂ Down byÂ SidneyÂ Sheldonâ€Â isÂ writtenÂ toÂ identifyÂ andÂ analyzeÂ theÂ phrasalÂ verbsÂ inÂ termsÂ ofÂ formÂ andÂ meaning. TheÂ methodÂ usedÂ isÂ descriptiveÂ method.Â TheÂ dataÂ areÂ takenÂ fromÂ theÂ novel,Â andÂ analyzed Â basedÂ onÂ theÂ conceptÂ ofÂ BeaumontÂ danÂ GringerÂ inÂ termsÂ ofÂ formÂ andÂ ThomsonÂ MartinetÂ forÂ theirÂ meanings. TheÂ writerÂ findsÂ thatÂ thereÂ areÂ fourÂ formsÂ ofÂ phrasalÂ verbsÂ inÂ theÂ novel, thoseÂ areÂ the first formÂ : verb + particle +,Â the second form : verb + particle + object andÂ verb + object + particle,Â the tirth formÂ : Verb + Particle + ObjectÂ inÂ whichÂ verbÂ cannotÂ beÂ separatedÂ fromÂ theÂ particle,Â and the fifth form : Verb + Particle + Preposition. TheÂ writerÂ alsoÂ findsÂ thatÂ thereÂ areÂ phrasalÂ verbsÂ thatÂ have Â moreÂ thanÂ oneÂ meaningsÂ thoseÂ are getÂ up,Â putÂ down,Â comeÂ back,Â talkÂ about,Â comeÂ up,Â finishÂ up,Â keepÂ up, Â makeÂ up,Â putÂ up,Â turnÂ up, setÂ ofÂ andÂ giveÂ up. ThisÂ researchÂ couldÂ helpÂ theÂ readerÂ toÂ increaseÂ theÂ knowledgeÂ especiallyÂ on phrasalÂ verbsÂ andÂ toÂ understand phrasal verb in the novel The Stars Shine Down deeply. Â KeyÂ words : English phrasal verb,Â TheÂ StarsÂ ShineÂ Down.